PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP PERKEMBANGAN KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK KELAS X SMA PEMBANGUNAN LABORATORIUM UNP - Saswandila, Azizah (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical Representation ability is one of the abilities needed in learning mathematics. However, in fact, this ability category of SMA Pembangunan Laboratorium UNP 10th-grade students was still low. The effort that was argued to overcome this problem is by applying the Realistic Mathematics Education (RME) approach. The research objective was to describe the improvement of students’ mathematical representation ability during being taught using the RME approach. The method used is quantitative descriptive. The sampling technique is purposive sampling. The instrument of this research is quizzed consisting of essay questions. Based on data analysis, the improvement of students’ mathematical representation ability generally was increased during being taught using the RME approach,Keywords–Realistic Mathematics Education (RME), Mathematical Representation Ability